Алгебро-логічні рівняння для пошуку аналогій в навчальних розподіленних ресурсах - Тітов, Г. О. (ХНУРЕ, 2024)
This work explores the application of algebraic equations in uncovering patterns and analogies within diverse datasets. By utilizing algebraic equations, the study delves into the systematic analysis of various types of data, aiming to reveal underlying regularities and relationships. The flexibility of algebraic equations allows adaptation to a wide range of data types, including numerical, textual, and categorical formats. The research highlights the role of algebraic equations in enhancing machine learning capabilities, ensuring statistical rigor, and addressing real-world challenges.
Keywords: алгебро-логічні рівняння; пошук аналогій; навчальні ресурси